Pelaksanaan Evaluasi Afektif Pada Kurikulum 2013 di Sekolah Dasar Se Kota Padang - Abna Hidayati ,M. Pd (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
Evaluation is an important part of the learning process. In the evaluation of the realm of learning there are three aspects, cognitive, affective and psychomotor. The use of the instrument in the implementation of aspects of the votes in the field is still a lot of attitudes have constraints, which created difficulties with teacher assessment system has varied assessment instruments. so that not all the instruments that can be used by teachers. This study aims to determine how the evaluation of affective on the curriculum in primary schools at 2013 in Padang.This research is a quantitative research is descriptive. The population in this study is an elementary school in Padang wearing Curriculum 2013, while a sample is taken from a representative from the District to apply Curriculum 2013 that the District 6 by 9 primary schools. Instruments used to collect data in the form of a questionnaire. The data were analyzed by descriptive quantitative and presented in tabular form. The results showed that: the use of instruments for assessing the competence of attitude, covering the preparation, implementation and processing by teachers is quite good because of the use of the instruments on each competency has been used well. Based on the above data it can be concluded that the implementation of the Curriculum assessment affective aspects of elementary schools in 2013 in the city of Padang classified in the category quite well. Suggestions in this study teachers to make use of assessment instruments relevant attitude aspects.